(untitled) (Jurnal Social Science, 2023)
Tourism activities require adequate facilities infrastructure and accommodation This study aims to identify aspects of the facilities infrastructure and accessibility of Paal Beach and Pelican Beach tourism objects The research method uses a quantitative empirical approach Data collection techniques include observation questionnaires documentation and literature studies Data analysis with scoring analysis The results of the research show that the condition of facilities and accessibility is quite adequate Meanwhile the condition of the infrastructure for Paal Beach and Pelican Beach attractions is in a low category < em>< p>